2012
DOI: 10.3109/02713683.2012.700754
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protective Effects of Trehalose on Desiccation of Epithelial Cells in Three Dimensional Reconstructed Human Corneal Epithelium

Abstract: CLSM and an in vitro cell viability assays could be successfully used for the characterization of 3D-HCE tissue. We demonstrated the protective role of trehalose using reconstructed corneal epithelium (3D-HCE), which mimics HCE and has the potential to become a valuable model in ophthalmic research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…The mechanisms of TH in protecting corneal epithelial cells have been reported in some details (Izawa et al 2006;Luyckx & Baudouin 2011;Hovakimyan et al 2012;Hill-Bator et al 2014) and include water replacement in the desiccated cells by hydrogen bonding interactions with polar groups on membrane lipids and proteins (Leidy et al 2004), modification of the tetrahedral hydrogen-bond structure of water and rearrangement of the remaining water molecules around biological structures (Teramoto et al 2008) and reduced tendency to form crystals that can damage cell organelles (Luyckx & Baudouin 2011). These bioprotective effects of TH have also been proven in a number of clinical studies (Matsuo 2004;Ramoth et al 2013;Pinto-Bonilla et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of TH in protecting corneal epithelial cells have been reported in some details (Izawa et al 2006;Luyckx & Baudouin 2011;Hovakimyan et al 2012;Hill-Bator et al 2014) and include water replacement in the desiccated cells by hydrogen bonding interactions with polar groups on membrane lipids and proteins (Leidy et al 2004), modification of the tetrahedral hydrogen-bond structure of water and rearrangement of the remaining water molecules around biological structures (Teramoto et al 2008) and reduced tendency to form crystals that can damage cell organelles (Luyckx & Baudouin 2011). These bioprotective effects of TH have also been proven in a number of clinical studies (Matsuo 2004;Ramoth et al 2013;Pinto-Bonilla et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose-containing eyedrops have previously been shown to be effective in in vitro, 9 , 10 ex vivo, 11 and in vivo animal studies 12 as well as in a few clinical studies. 13 15 A further advantage of this formulation is a longer residency time than hyaluronate alone, as recently shown in a randomized, double-masked study.…”
Section: Discussionmentioning
confidence: 99%
“…and water efflux resulting in cell shrinkage, distortion and preferential hydration (Huang and Tunnacliffe 2007). A wide variety of pre-incubation times have been documented for trehalose; for instance, Wikstr€ om et al (2012) reported an upper pre-incubation period of 12 days for the cryopreservation of microencapsulated human retinal pigment epithelial cells, while on the other extreme, the pre-incubation period was limited to 15 min for human corneal epithelium cells in 2D (Hovakimyan et al 2012).…”
Section: Effect Of Cell Culture Condition and Trehalose On Hek Cell Vmentioning
confidence: 99%